Pemberdayaan Masyarakat Petani Bawang Merah melalui Pengolahan Bawang yang Tidak Terjual Menjadi Bawang Goreng - Iis Komariah; Anton Anton; Acep Rahmat; Fiqra Muhamad Nazib (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Shallots are one of the horticultural commodities that are really needed by the community, where this red onion commodity has become a source of income and employment opportunities and has made quite a high contribution to the economic development of a region, especially in several regions in Indonesia, especially the West Java region which is one of the largest producers of shallots. Several areas that have great potential, such as Garut, Cirebon, Majalengka and Bandung, are producers of shallots in West Java. On this occasion, we carried out service that focused on the Garut district area where shallot farming is the largest area managed by the people of Garut district. The aim of the empowerment carried out is to use unsold shallots into a fried onion production business to improve the community's economy, which is carried out through analyzing problems in the field, gathering farmer residents, providing counseling, technical training and assistance on how to process raw shallots into fried onions. has economic value so that a processing method that is effective, efficient and has high selling value is found as people's need for fried onions continues to increase.